Peran Guru PAI Dalam Menanamkan Sikap Sosial Bagi Siswa Kelas VII di MTs Negeri Kota Tanjungbalai - Arlina Arlina; Khairun Nisa Marpaung; Sylva Rahmah Hafiz; Anita Dewi; Putri Azida Manurung; Siti Syaidariah Hasibuan; Shofwan Agil Muwazif (Jurnal Dirosah Islamiyah, 2023)
Purpose of this study was to find out how the role of PAI teachers, especially teachers of the Aqidah Akhlak subject, in instilling social attitudes towards today's class VII students at MTs Negeri Tanjung Balai. The method used in this study is a qualitative descriptive method with a phenomenological approach. Data collection techniques are carried out through observation, interviews and documentation. The informant used was the Tanjung Balai State MTs Akidah Akhlak teacher. The results of the study show that teachers have made many efforts to instill social attitudes in students. This can be seen from, 1) Islamic religious education teachers who play a role in instilling an attitude of discipline and responsibility by providing direct guidance, setting good examples, directions, advice, and even punishment to students who commit acts of fighting and violations of school rules .2) Islamic religious education teachers who play a role in instilling a caring attitude towards students who commit acts of bullying by providing guidance, advice and making various activities that can establish good interactions between students and create harmony. 3) Islamic religious education teachers who play a role in instilling an attitude of respect by treating students as their own biological children, loving and caring for students, respecting the existence of students, not making students feel small and establishing good relationships with students, so students can have respectful attitudes to teachers and have manners and ethics in dealing with both teachers, parents and peers. Keywords: Role of PAI Teachers, Social Attitudes of Students